Evaluating the effects of black pepper and white vinegar on E. coli K12 in round steak - Hall, Carter; Jensen, K.; Jolliffe, I.; Goerl, A.; Harbert, A.; Herl, Bethany; Lawrence, J.; Kozenko, Brittany; Jones, Cassandra K.; Trinetta, Valentina (My University, 2017)
Introduction: Escherichia Coli is one of the most well-known pathogens due to its persistence even in modern countries. Raw or undercooked meat possess one of the greater opportunities for infection. Safe at-home procedures to decontaminate meat becomes necessary to reduce E. Coli prevalence. Effective procedures that do not hinder quality are ideal solutions. Purpose: The objective of this study was to determine if application of vinegar or pepper hindered and/or reduced the presence of E. Coli on whole beef. Methods: McConkey, PDA, and PCA plates were used to detect amount of E. Coli, Yeast and Molds, and total microbial colonies. 4 samples of whole muscle beef were used. 3 were inoculated with 300ul of E. Coli and the 4th was kept as a negative control. One inoculated sample was the positive control and the remaining two were exposed to either 250ml of white vinegar or 5g of pepper. 10g samples were taken from each piece of beef and sampled over the course of 7 days for growth. Results: Of the two treatments, vinegar showed a statistically significant reduction in E. Coli, yeast, and mold growth. The reduction occurred within the first 24 hours of treatment and then maintained itself throughout the remainder of the experiment. Pepper showed no significant reduction in E. Coli growth. Significance: The results of this study suggest that a piece of whole muscle beef marinated with vinegar for as little as 24 hours significantly decreases the likelihood of E. Coli infection. This allows for, when using a white vinegar marinade, the safe consumption of undercook or contaminated meat.
Keywords: Fall 2017